Small Molecule, Big Prospects: MicroRNA in Pregnancy and Its Complications - Meng Cai; Gopi K. Kolluru; Asif Ahmed (Journal of Pregnancy)
MicroRNAs are small, noncoding RNA molecules that regulate target gene expression in the posttranscriptional level. Unlike siRNA, microRNAs are “fine-tuners” rather than “switches” in the regulation of gene expression; thus they play key roles in maintaining tissue homeostasis. The aberrant microRNA expression is implicated in the disease process. To date, numerous studies have demonstrated the regulatory roles of microRNAs in various pathophysiological conditions. In contrast, the study of microRNA in pregnancy and its associated complications, such as preeclampsia (PE), fetal growth restriction (FGR), and preterm labor, is a young field. Over the last decade, the knowledge of pregnancy-related microRNAs has increased and the molecular mechanisms by which microRNAs regulate pregnancy or its associated complications are emerging. In this review, we focus on the recent advances in the research of pregnancy-related microRNAs, especially their function in pregnancy-associated complications and the potential clinical applications. Here microRNAs that associate with pregnancy are classified as placenta-specific, placenta-associated, placenta-derived circulating, and uterine microRNA according to their localization and origin. MicroRNAs offer a great potential for developing diagnostic and therapeutic targets in pregnancy-related disorders.